2018
DOI: 10.1371/journal.pone.0199147
|View full text |Cite
|
Sign up to set email alerts
|

Feasibility, benefit and risk of systematic intraoperative cholangiogram in patients undergoing emergency cholecystectomy

Abstract: BackgroundThe role of intraoperative cholangiogram (IOC) during cholecystectomy is debated. The aim of the present study was to evaluate the feasibility, benefit and risk of performing systematic IOC in patients undergoing cholecystectomy for acute gallstone-related disease.MethodsBetween July 2013 and January 2015, all patients admitted for an acute gallstone-related condition and undergoing same-hospital-stay cholecystectomy were prospectively followed. IOC was systematically attempted and predictors of IOC … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
10
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 27 publications
2
10
0
Order By: Relevance
“…Similarly, another study determined that the predictive value of IOC was around 50% resulting in several unnecessary postoperative procedures. 25 Our rate of false-positive IOC was 3.4% (2 of 58 filling defects on IOC). Two patients underwent unnecessary interventions because of false IOC images suggesting CBD stones.…”
Section: Discussionmentioning
confidence: 58%
“…Similarly, another study determined that the predictive value of IOC was around 50% resulting in several unnecessary postoperative procedures. 25 Our rate of false-positive IOC was 3.4% (2 of 58 filling defects on IOC). Two patients underwent unnecessary interventions because of false IOC images suggesting CBD stones.…”
Section: Discussionmentioning
confidence: 58%
“…A selective policy of IOC use was adopted in 14 studies with a mean IOC use of 16.7% (2.8%–36.9%) in 12,064 patients [ 18 , 19 , 34 , [37] , [38] , [39] , [40] , [41] , [42] , [43] , [44] , [45] , [46] , [47] ]. Additionally, 14 studies adopted a policy of routine IOC with a mean average use of 88.3% (63.5%–99.2%) in 25,072 patients [ 17 , 19 , 34 , 37 , 42 , [48] , [49] , [50] , [51] , [52] , [53] , [54] , [55] , [56] ].…”
Section: Resultsmentioning
confidence: 99%
“…Eleven studies ( n = 10,466) reported the incidence of CBD stones on routine IOC with a mean of 11.8%, ranging from 2.8% to 18.9% [ 19 , 34 , 37 , 38 , [50] , [51] , [52] , [53] , [54] , [55] , [56] ]. Eight studies ( n = 4,556) reported the incidence of CBD stones on selective IOC with a mean of 3.9%, range 0.7% to 12.8% [ 18 , 19 , 34 , [37] , [38] , [39] , 44 , 45 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…2,4,[8][9][10] Previously, it has been shown that IOC identifies a common bile duct stone (CBD) in 22.4% of cases when performed in all patients undergoing cholecystectomy for gallstone-related disease and that in 29% of these patients with a CBD stone, IOC was the first imaging modality to identify a stone. 17 Further analysis with a broader access to variables such as patient symptoms and laboratory values at presentation may aid in identifying which patients are most likely to benefit from increased IOC use so that resources can be most effectively allocated. Although previous studies have reported increased risk of complications and unplanned admission with IOC, 8 this was not supported by our cohort.…”
Section: Discussionmentioning
confidence: 99%